REORIENTASI PERAN POLRI DALAM PENANGANAN KONFLIK SOSIAL DARI PERSPEKTIF PENEGAKAN HUKUM - Suparmin Suparmin (Masalah-Masalah Hukum, 2014)
Reorientation of Police who played the role in conflict resolution must be done. Another aim is to understand the strategies and social conflict handling mechanisms to achieve peace is in line with the demands of law, democracy , justice and truth, as well as human rights. The research found that the handling of social conflicts, Police as law enforcement responsible for maintaining security in the country are required to have expertise and skills professionally and proportionately in line with the demands of law, democracy, justice and truth, as well as human rights.